Penetrating Sacral Injury with a Wooden Foreign Body - Arash Fattahi; Amin Jahanbakhshi; Ardeshir Shahivand; Alireza Dastmalchi (Case Reports in Medicine)
Spinal penetrating trauma has a complex neurosurgical management. This study presents a 55-year-old male admitted in our center with a 1 × 1 centimeter laceration on the sacral area skin due to a wooden penetrating object. The computed tomography (CT) of the spine revealed a hypodense penetrating object that was introduced from the posterior aspect of the sacrum into dural space and then stopped in the S1 vertebral body. We performed a laminectomy of intact superior portion of the S1 lamina and released the wood from the surrounding bone, and finally, we pulled it out.